Production of a promotional video for the Ranca Upas Camping Ground during the new normal period of the Covid-19 pandemic - Syifaul Fuada; Leonardi Paris Hasugian; Fitri Fitriah; Hashina Qiamu Mumtaziah (Community Empowerment, 2023)
During the pandemic, the lack of information dissemination on Ranca Upas Camping Grounds resulted in a lack of visitors because they were not aware of the health protocols that had been implemented. The community service aims to help disseminate information by making a promotional video containing the application of 3M and equipment for implementing health protocols in tourism areas. The aim is to support the management in promoting Ranca Upas Camping Ground Tourism so that it can attract tourists to return to traveling during the new normal period. The method of implementing community service activities consists of the preparation stage, implementation, and evaluation. This activity produces digital products in the form of promotional video as an effort to recover tourism visitors from Ranca Upas Camping Grounds in adapting to new habits. The tourism manager stated that the product helps in disseminating information so that tourists can find out about the health protocols that have been implemented.